2009
DOI: 10.1623/hysj.54.1.189
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the rainy season precipitation in central Jordan

Abstract: Concurrent reconstructions of October-April precipitation at Madaba and Rabba gauging sites in central Jordan back to the year 1777 using a multivariate regression model are presented. The reconstruction model was calibrated using concurrent precipitation and tree-ring data for the period 1953-1981 The regression equation is significant (p < 0.05), while reconstructions account for 53% and 48% (adjusted for lost degrees of freedom) of the total variability of the precipitation at the Madaba and Rabba sites, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Over the 239 years, the reconstructed precipitation could not copy the magnitude of the largest single year wet event recorded in 1992, which can be explained as a result of two combined factors. The first is attributed to the reconstruction model (regression model) that explained about 53% of the historical precipitation total variability (Tarawneh & Hadadin ). Reconstruction models partial variability explanation was observed in other research (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Over the 239 years, the reconstructed precipitation could not copy the magnitude of the largest single year wet event recorded in 1992, which can be explained as a result of two combined factors. The first is attributed to the reconstruction model (regression model) that explained about 53% of the historical precipitation total variability (Tarawneh & Hadadin ). Reconstruction models partial variability explanation was observed in other research (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study (Tarawneh & Hadadin ), the rainy season precipitation for Madaba was reconstructed using the Multivariate Regression model back to the year 1743 benefiting of tree‐ring indices from nearby tree sites (Dana Reserve and Tor Al‐Iraq in Jordan, Ceadar Valley – Trocken and Plano Platres – Feucht in Cyprus). Figure shows the reconstructed rainy season precipitation for Madaba over the period 1743–1981.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Funhermore, droughts of extreme magnitude and short duration lasting 1-3 years were observed by a dendroclimatological study of the region of Southern Jordan, with an average time interval between drought events of 4.2 years (Touchan et al, 1999). Likewise, a joint analysis of reconstructed precipitation at two sites in the central Jordan region showed that regional droughts of short duration (1-3 years) are the most recunent events, with a retum period of about 3.8 years (Tarawneh & Hadadin, 2009). Theoretical models have also been used to investigate the distribution, occurrence probability and retum period of droughts, considering drought length only (e.g.…”
Section: Introductionmentioning
confidence: 99%